Digitalization and Sustainability Indicators for SMI Resilience in Developing Economies: A Conceptual Model from Padang City of Indonesia - Rini Syahfitri; Elita Amrina; Insannul Kamil (Jurnal Optimasi Sistem Industri, 2025)
The application of digital technology increases productivity, expands market reach, helps small and medium industries (SMIs) adapt to various changes, and provides a great contribution to sustainability. Sustainability emphasizes the importance of maintaining economic, environmental, and social balance in the long term, while resilience describes the ability of SMIs to confront and recover from various disruptions. However, the SMIs in Padang are less aware of the importance of implementing digitalization sustainably to achieve SMI resilience. Several indicators remain unmet by SMIs. This study aims to compile and validate digitalization and sustainability indicators appropriate to the context of local SMIs. These indicators were collected from various literature sources that include digital literacy, digital marketing, economic, environmental, and social sustainability, and resilience aspects. The validation process involved five experts from academia, government, and industry practitioners selected based on their expertise in the fields of the aforementioned aspects. Experts assessed the relevance and clarity of each indicator using the Likert scale, then the results were analyzed with the Aiken index and tested for reliability between assessors using SPSS to ensure consistency of assessments. The results of the study show that these indicators are aligned with the dimensions measured, particularly those that affirm the importance of digital literacy, digital marketing, and social aspects of sustainability in strengthening the resilience of SMIs. These validated indicators were then used to develop a conceptual model that can be a strategic reference for stakeholders and policymakers to increase the competitiveness, resilience, and sustainability of SMIs in Padang.